The solution structure of a [3Fe-4S] ferredoxin: oxidised ferredoxin II from desulfovibrio gigas - Goodfellow, B. J. (2014)
The use of standard 2D NMR experiments in combination with 1D NOE experiments allowed the assignment of 51 of the 58 spin systems of oxidised [3Fe-4S] ferredoxin isolated from Desulfovibrio gigas. The NMR solution structure was determined using data from 1D NOE and 2D NOESY spectra, as distance constraints, and information from the X-ray structure for the spin systems not detected by NMR in torsion angle dynamics calculations to produce a family of 15 low target function structures. The quality of the NMR family, as judged by the backbone r.m.s.d. values, was good (0.80 Å), with the majority of f/c angles falling within the allowed region of the Ramachandran plot. A comparison with the X-ray structure indicated that the overall global fold is very similar in solution and in the solid state. The determination of the solution structure of ferredoxin II (FdII) in the oxidised state (FdIIox) opens the way for the determination of the solution structure of the redox intermediate state of FdII (FdIIint), for which no X-ray structure is available.